Jack of all trades: Genome assembly of Wild Jack and comparative genomics of Artocarpus - Patil, Ajinkya Bharatraj; Vajja, Sai Samhitha; Raghavendra, S.; Satish, B. N.; Kushalappa, C. G.; Vijay, Nagarjun (Frontiers in Plant Science, 2022)
Artocarpus (Moraceae), known as breadfruits for their diverse nutritious fruits, is prized for its high-quality timber, medicinal value, and economic importance. Breadfruits are native to Southeast Asia but have been introduced to other continents. The most commonly cultivated species are Artocarpus heterophyllus (Jackfruit) and Artocarpus altilis (Breadfruit). With numerous smaller but nutritionally comparable fruits on a larger tree, Artocarpus hirsutus, also called "Wild Jack" or "Ayani", is an elusive forest species endemic to Indian Western Ghats. In this study, we sequenced and assembled the whole genome of Artocarpus hirsutus sampled from the sacred groves of Coorg, India. To decipher demographic and evolutionary history, we compared our Wild Jack genome with previously published Jackfruit and Breadfruit genomes. Demographic history reconstruction indicates a stronger effect of habitat rather than phylogeny on the population histories of these plants. Repetitive genomic regions, especially LTR Copia, strongly affected the demographic trajectory of A. heterophyllus. Upon further investigation, we found a recent lineage-specific accumulation of LTR Copia in A. heterophyllus, which had a major contribution to its larger genome size. Several genes from starch, sucrose metabolism, and plant hormone signal transduction pathways, in Artocarpus species had signatures of selection and gene family evolution. Our comparative genomic framework provides important insights by incorporating endemic species such as the Wild Jack.